Quintais produtivos: do saber ao fazer segurança alimentar no assentamento Zumbi dos Palmares em Mari, Paraíba - Soares, Ailsa Cristiane Arcanjo (2020)
Productive backyards are multifunctional spaces that are very present in the context of family farming. These spaces present in the productions of the farming families their cultural characteristics, through specific techniques and also regional plants capable of guaranteeing the food security of the families. The present work was elaborated from a case study with the objective of verifying what is produced in the productive backyards in the Zumbi dos Palmares settlement in the municipality of Mari, in the state of Paraíba, analyzing its diversity and its contribution to food security and income of farming families. The methodology used was qualitative and quantitative and the instruments used were semi-structured interviews, as well as informal conversations in 41 batches of family farmers who had productive yards in the settlement. There was also a tour for a better observation of the productions as well as for the photographic records. In the results, we found 13 animal species, from seven different families and 87 plant species, with 45 different families, among fruit, medicinal and tuber species, totaling 100 species in general. We conclude that the productive backyards of the Zumbi dos Palmares settlement show that, even with the relatively low number of species, animals and vegetables, but with the presence of several fruit and food species in the region, families maintain local food security and improve the composition family income with the sale of surpluses.